1997
DOI: 10.1177/07399863970192006
|View full text |Cite
|
Sign up to set email alerts
|

Examination of Self-Efficacy, Social Support, and Stress as Predictors of Psychological and Physical Distress among Hispanic College Students

Abstract: Social and cognitive factors were investigated to determine whether self-efficacy and social support moderate the relationship between stress, andphysical andpsychological distress among Hispanic college students. A total of 164 Mexican American and Latin American undergraduates were surveyed (51% response rate). Self-efficacy and social support combined to account for 33% of the variance in college adjustment, with self-efficacy providing the largest contribution (R2Change 27%o). Hispanic students who perceiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
138
2

Year Published

1998
1998
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(153 citation statements)
references
References 27 publications
13
138
2
Order By: Relevance
“…For this sample, students' perceived self-efficacy was not predictive of their success on the national Registry exam. These results do not support the findings of previous studies that included self-efficacy as a predictor variable (Chemers et al, 2001;House, 1993bHouse, , 2001Solberg & Villareal, 1997;Wilhite, 1990). With different measures of self-efficacy, samples, settings, and dependent variables, self-efficacy was found to be a significant predictor in these studies.…”
Section: Research Question #4contrasting
confidence: 99%
See 1 more Smart Citation
“…For this sample, students' perceived self-efficacy was not predictive of their success on the national Registry exam. These results do not support the findings of previous studies that included self-efficacy as a predictor variable (Chemers et al, 2001;House, 1993bHouse, , 2001Solberg & Villareal, 1997;Wilhite, 1990). With different measures of self-efficacy, samples, settings, and dependent variables, self-efficacy was found to be a significant predictor in these studies.…”
Section: Research Question #4contrasting
confidence: 99%
“…Students who perceived social support to be available were found to have less distress ratings than students who perceived less social support. Solberg and Villareal (1997) concluded that self-efficacy expectations may be an important predictor of college persistence. One limitation of this study was that social support was not defined, therefore it was unclear who participants considered to be a support person.…”
Section: Self-efficacy Persistence and Grade Predictionmentioning
confidence: 99%
“…This finding was similar with that of Cohen and Wills (1985) and Azila-Gbettor et al, (2015) who found that social support was found to buffer stress. Along with this, Solberg (1997) clarified that perceived social support moderates the relationship between stress and distress and those who had higher perception of social support had lower distress rating. Furthermore, Cohen (1988); Eckenrode and Wethington (1990); Coyne and Downey (1991) and Deihl et al, (1997) disclosed that parental social support has been correlated with level of stress among students.…”
Section: Academic Achievement Stress Levelmentioning
confidence: 73%
“…Young Latina students often find themselves at PWI's and they must adjust to the environment, which results in stress, especially if the student lacks social support. Solberg and Viliarreal (2007) found that stress is an important factor for Latino students. Students who perceive social support have lower distress levels.…”
Section: Strategies That Improve Success Of the Latina College Studentsmentioning
confidence: 99%
“…Students who perceive social support have lower distress levels. College graduation rates can be enhanced if institutions work to enhance social support networks, develop intervention programming, and facilitate self-efficacy expectations (Solberg & Viliarreal, 2007). A recent study conducted by Gloria et al (2005) assessed the degree to which social support, university comfort, and selfbeliefs were interrelated and predictive of undergraduate Hispanic students' decisions to persist.…”
Section: Strategies That Improve Success Of the Latina College Studentsmentioning
confidence: 99%